Trito-Isaiah (Isaiah 56-66) and the gôlāh group of Ezra, Shecaniah, and Nehemiah (Ezra 7-Nehemiah 13): Is there a connection?. (June 2019) - Blenkinsopp, Joseph
This essay addresses the issue of a possible connection between Trito-Isaiah and Ezra-Nehemiah, in the sense of the former promoting or opposing the agenda of Ezra, Nehemiah, and the gôlāh group associated with them. The first stage is to determine the dating of the relevant texts. According to the biblical dating, the activity of Ezra and Nehemiah falls within the quarter-century 458–432 BC. Some of the more significant textual components of Trito-Isaiah—the communal lament of Isa 63:7-64:11, the anti-Edomite polemic in Isa 63:1-6, and especially the core section 60-62—are manifestly earlier. The most prominent themes in Isaiah 56-66—Zion and the Servants of the Lord—are absent from Ezra-Nehemiah. In Ezra 9:4 and 10:3, the hărēdim are dominant, while those of Isaiah 66:2, 5 are a despised and rejected group, probably identical to the Servants of the Lord of Isa 65:8-16 and 66:14-16.